Enhancing Silicon Anode Performance in Lithium-Ion Batteries Through Hybrid Artificial SEI Layer and Prelithiation - Bo Peng; Weizhai Bao; Kaiwen Sun; Jin Xiao (Nanomaterials)
Prelithiation has been widely accepted as one of the most promising strategies to compensate for the loss of active substance and to improve the initial Coulombic efficiency in silicon-based anodes for advanced high-energy-density batteries. But because of their unstable solid electrolyte interface (SEI) layer and low initial Coulombic efficiency, they expand in volume during prelithiation and react with moisture, which makes commercialization a difficult process. Herein, we have developed a strategy using lithium bis(fluorosulfonyl)imide (LiFSI) treatment to eliminate redundant lithium and generate LiF-based inorganic compounds on the surface of the prelithiated electrode. Such method not only reduces the reactiveness of the prelithiated anode but also enhances the ionic conductivity of the SEI. The rich LiF surface works as an artificial SEI, and according to electrochemical evaluation, the initial Coulombic efficiency of the prelithiated silicon anode treated with LiFSI can reach 92.9%. This technique not only increases the battery’s energy density but also its cycle stability, resulting in superior capacity retention and a longer cycling life.